A Performance Comparison of HPC Workloads on Traditional and Cloud-Based HPC Clusters - Munhoz, Vanderley; Bonfils, Antoine; Castro, Márcio; Mendizabal, Odorico (Anais Estendidos do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2023)
Cloud Computing allows users to access large computing infrastructures quickly. In the High Performance Computing (HPC) context, public cloud resources emerge as an economical alternative, allowing institutions and research groups to use highly parallel infrastructures in the cloud. However, parallel runtime systems and software optimizations proposed over the years to improve the performance and scalability of HPC applications targeted traditional on-premise HPC clusters, where developers have direct access to the underlying hardware without any kind of virtualization. In this paper, we analyze the performance and scalability of HPC applications from the NAS Parallel Benchmarks suite when running on a virtualized HPC cluster built on top of Amazon Web Services (AWS), contrasting them with the results obtained with the same applications running on a traditional on-premise HPC cluster from Grid'5000. Our results show that CPU-bound applications achieve similar results in both platforms, whereas communication-bound applications may be impacted by the limited network bandwidth in the cloud. Cloud infrastructure demonstrated better performance under workloads with moderate communication and medium-sized messages.